Effect-enhancing and toxicity-reducing effects of Chaihu Jia Longgu Muli decoction in the treatment of multimorbidity with depression: a systematic review and meta-analysis - Xurui Jia; Jie Chen; Ruiou Huang; Dawei Wang; Xing Wang (Taylor & Francis Group, 2023)
AbstractContext Chaihu Jia Longgu Muli Decoction (CLMD) is a traditional Chinese medicine for treating depression.Objective This study investigated the effect of CLMD combined with antidepressants on multimorbidity with depression (MMD).Method Published randomized controlled trials were collected from PubMed, Web of Science, Chinese National Knowledge Infrastructure, China Science and Technology Journal, Wanfang and China Biomedical Literature Service System Databases. Participants were divided into study groups (CLMD combined with antidepressants) and control groups (antidepressants). RevMan5.4 software was used for data analysis.Results Hamilton's Depression Scale score was significantly lower (MD = −5.62, 95%CI [−5.86, −5.37], p < 0.00001), and the effective rate was significantly higher (RR = 1.23, 95%CI [1.17, 1.29], p < 0.00001) in study groups. National Institute of Health Stroke Scale score and Pittsburgh Sleep Quality Index score of study groups were significantly lower (MD = −2.82, 95%CI [−3.84, −1.81], p < 0.00001; MD = −2.26, 95%CI [−3.19, −1.34], p < 0.00001). 5-HT, DA, NE and IL-1β level were significantly lower (SMD = 1.99, p = 0.003; SMD = 1.99, p < 0.00001; SMD = 0.86, p < 0.00001; MD = −14.64, p = 0.003) in study groups. Adverse reaction rate in study groups was significantly lower (RR = 0.47, 95%CI [0.24, 0.91], p = 0.03). The gastrointestinal tract and autonomic nervous system disorders were reduced in study groups.Discussion and conclusions CLMD combined with antidepressants enhances the effect of antidepressants and reduces their adverse reactions, performing a synergistic effect; it may be considered as an effective option in the treatment of MMD.